Sustainability Report of the Oil Palm Sector 2018-2021 - Federación Nacional de Cultivadores de de Palma de Aceite, Fedepalma (Federación Nacional de Cultivadores de de Palma de Aceite., 2022)
A sustainable and reliable origin that creates the highest value for palm grower and has a positive impact for the environment and palm-growing communities
Keywords: Palma de aceite; Aceite de palma; Sostenibilidad; Agroindustria de la palma de aceite; Economía; Producción; Empleo; Objetivos de Desarrollo Sostenible; Gestión ambiental; Certificación